Flag Raising at Red House - (:unkn) unknown (Art Photo Studio, Trinidad, 2010)
Historic August 31st 1962 postcard showing an external view of the Red House with the Trinidad and Tobago flag raised for the first time. The Red House is the seat of Parliament in the Republic of Trinidad and Tobago. The original building was destroyed in the water riots, 1903 and the landmark was rebuilt in 1907. Postcard number 67883-B.
Colour: Red, Blue, Black and White ; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Red House, The